2007
DOI: 10.1063/1.2794226
|View full text |Cite
|
Sign up to set email alerts
|

A new parallel plate shear cell for in situ real-space measurements of complex fluids under shear flow

Abstract: We developed and tested a parallel plate shear cell that can be mounted on top of an inverted microscope to perform confocal real-space measurements on complex fluids under shear. To follow structural changes in time, a plane of zero velocity is created by letting the plates move in opposite directions. The location of this plane is varied by changing the relative velocities of the plates. The gap width is variable between 20 and 200 microm with parallelism better than 1 microm. Such a small gap width enables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 50 publications
3
35
0
Order By: Relevance
“…Previous measurements showed that in the parallel plate shear cell, the flow profile of a dilute colloidal suspension of these silica particles in ETPTA at a volume fraction of ϭ 0.22 was linear as expected (46). However, the flow profile of a partially crystallized suspension deviated from linearity.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous measurements showed that in the parallel plate shear cell, the flow profile of a dilute colloidal suspension of these silica particles in ETPTA at a volume fraction of ϭ 0.22 was linear as expected (46). However, the flow profile of a partially crystallized suspension deviated from linearity.…”
Section: Resultsmentioning
confidence: 88%
“…The counterrotation principle creates a plane of zero velocity in which a collection of particles can be tracked for an extended time. In the present work, we also used a counter translating parallel plate shear cell with a small enough plate separation that we could observe individual particles throughout the gap with a confocal microscope (46). This enabled us to obtain local information about the complete system.…”
mentioning
confidence: 99%
“…II-IV, we have demonstrated that our confocal rheoscope accurately measures the structural and stress responses of a complex fluid in a precisely controlled shear flow. Similar to other confocal rheometers 23,25,[29][30][31][32][33][35][36][37][38][39][40][41][42][43][44] this instrument allows us to investigate the interplay between a suspension's structure and its rheology. However, our device also allows for biaxial rheological measurements and the study of confined systems.…”
Section: Applicationsmentioning
confidence: 99%
“…23,29,31,33,[39][40][41][42][43][44] Again, the simplest designs have one surface fixed in the laboratory frame, though independently moving both is possible and has the same advantages as in the analogous rotational design. 33,44 In these planar designs, with careful alignment of the boundaries, sample thicknesses of just a few particle diameters become possible, allowing exploration of thin film flow behaviors associated with confinement. 41,45,46 However, force measurement is a significant challenge in this flow geometry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation